Endovascular management of acute aortic dissection - Khayat, Mamdouh; Cooper, Kyle J.; Khaja, Minhaj S.; Gandhi, Ripal; Bryce, Yolanda C.; Williams, David M. (Cardiovascular Diagnosis and Therapy; Vol 8, Supplement 1 (April 13, 2018): Cardiovascular Diagnosis and Therapy (Advanced aortic imaging and intervention), 2017)
Abstract: Acute dissection of the thoracic aorta is a potentially life-threatening condition which requires collaborative treatment from multiple specialties for optimal patient outcomes. Dissections involving the ascending aorta and aortic arch have traditionally been managed entirely by surgery, while dissections beyond the arch vessels have most commonly been relegated to medical management. This algorithm has been undergoing a paradigm shift over the past two decades due to improvements in stent graft technology, better understanding of the hemodynamic interactions of the true and false lumen and their influence on organ and limb perfusion, and improvements in medical management and long term surveillance for dissection-related complications. This manuscript includes a brief discussion of the pathogenesis and etiology of dissection, followed by an in-depth review of the medical and endovascular techniques utilized to treat patients afflicted by this condition.